Pengaruh Perceived Value dan E-Service Quality Terhadap Kepuasan Konsumen pada Marketplace Shopee (Studi Kasus di Desa Suka Makmur Dusun II Kecamatan Delitua) - Syahfitri, Dinda Wulan; Fikri, Muhammad Hilman (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the effect of perceived value and e-service quality on consumer satisfaction in the Shopee marketplace (case study in Suka Makmur Village, Dusun II, Delitua District) partially and simultaneously. This research is quantitative research, with a population of 1228 people and a sample of 93 respondents using the Slovin formula, simple random sampling technique and data collection through observation and questionnaires. The research results show that perceived value has a positive and significant effect on consumer satisfaction, e-service quality has a positive and significant effect on consumer satisfaction. The results of the F test show that perceived value and e-service quality simultaneously have a positive and significant effect on consumer satisfaction. The R-Square value shows that the coefficient of determination is 0.627 or 62.7% of the consumer satisfaction variable can be explained by the perceived value and e-service quality variables, while the remaining 37.3% is influenced by other variables not included in this research.